PLASMA CALCIUM, PHOSPHORUS AND MAGNESIUM PROFILE IN POSTPARTUM COWS FOLLOWING HORMONAL THERAPY - PATEL, P M; DHAMI, A J; KAVANI, F S (The Indian Journal of Animal Reproduction, 2011)
Recently calved HF cows (24) ofUniversity farm were monitored for weekly plasma profile of calcium, phosphorus and magnesium from the day of calving till 21 st week postpartum following GnRH (Receptal) and PGF 2 alpha (Lutalyse) treatment at 7th week in anestrus and subestrus cows (6 each, keeping equal number as control), respectively. The plasma calcium levels in subestrus cows were significantly higher as compared to anestrus cows at 7th, 8th, 17th and 21 s1 week postpartum, including overall mean (8.17±0.08 vs 7.72±0.08 mg/di), while phosphorus levels were lower throughout the postpartum period, but varied significantly at calving and then at 1st - 3rd and 13th week postpartum (overall mean 6.96±0.07 vs 7.12±0.06 mg/di). The calcium and phosphorus levels were low at calving in all the groups, and increased linearly and significantly throughout the postpartum period in subestrus cows. Further, the cows of GnRH treatment group, in comparison to control, had significantly lower calcium levels at 1 s1, 5th, 8th and 19th weeks postpartum, butthis trend was inversed between PGF 2a treatment and control groups. The mean plasma Ca:P ratio was higher throughout the postpartum period in subestrus cows a compared to anestrus cows, and it differed significantly at 13th , 17th - 18th and 21st week postpartum. The magnesium levels of anestrus and subestrus cows (2.95±0.04 vs 3.14±0.01 mEq/L) did not differ significant at any of the intervals postpartum. Throughout the postpartum period magnesium levels were lower in GnRH treatment than the control group, but varied significantly only at 5th-10th and 13th- 15th week postpartum, whereas it was higher in PGF 2aipha treatment than the control group, and differed significantly from calving to 4th week.and again from 14th-20th week postpartum. The trend of plasma calcium, phosphorus levels reflected physiological/homeostatic mechanism of mineral metabolism and the hormone GnRH or PGF 2a treatment did not influence it.